Video Assisted Thoracic Surgery (VATS) in Constrictive Pericarditis - An Institutional Experience - Govini Bala Subramanian; Sonti Sulochana; Jalavadi Manohar (Dr. Annil Mahajan, 2024)
Constrictive pericarditis is a fibrous thickened pericardial layer which leads to reduced diastolic filling and right heart failure. It is due to inflammation and fibrosis of the pericardium caused by previous cardiac surgery or mediastinal radiotherapy. Once the disease is diagnosed, pericardiectomy is the standard treatment There are many techniques and approaches have been described for the procedure, but video assisted thoracic surgery (VATS) procedure is good, done mainly in European countries. In India it was rare to used. So, this study focuses on VATS in the management of constrictive pericarditis.